2010
DOI: 10.1590/s1415-790x2010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among workers in plastic manufacturing plants

Abstract: Background: Epidemiological studies have indicated an association between musculoskeletal disorders (MSDs) and physical work demands. Psychosocial work demands have also been identified as possible risk factors, but findings have been inconsistent. Objectives: To evaluate factors associated with upper back, neck and upper limb MSD among workers from 14 plastic manufacturing companies located in the city of Salvador, Brazil. Methods: A cross-sectional study design was used to survey a stratified proportional ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
22

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 21 publications
(23 reference statements)
3
27
0
22
Order By: Relevance
“…Data on working hours, extra shifts, overtime, employment time (whether formal or informal) and weekly hours at factory work were presented in another article 10 , which also includes data on weekly hours devoted to housework by men and women. Table 1 Prevalence of pain and musculoskeletal disorders * among plastics industry workers, according to body segment.…”
Section: Resultsmentioning
confidence: 99%
“…Data on working hours, extra shifts, overtime, employment time (whether formal or informal) and weekly hours at factory work were presented in another article 10 , which also includes data on weekly hours devoted to housework by men and women. Table 1 Prevalence of pain and musculoskeletal disorders * among plastics industry workers, according to body segment.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, for women, more intensely than for men, we can also add to paid work the responsibilities of the unpaid household work. The insufficient rest, more critical in women, could contribute to their illness 4,10,[18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…From these academic products, among others, some epidemiology articles were published on epidemiological prevalence of MSDs in this population 6 ; interaction between physical and psychosocial demands on the occurrence of low back pain 31 ; leisure physical activities and MSDs 32 ; interaction between physical fitness and physical demands at work on the occurrence of MSDs 33 ; validity and reproducibility of self-registration of the physical demands at work 34 ; and factors associated with MSDs in workers of this industry 21 . This latest exploratory study found an association between these diseases and female sex, psychosocial demands, and job dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido foi possível concluir que a coluna vertebral é muito exigida durante o atendimento do paciente. Assim esta atividade por exigir a execução de força, aliada a inclinação de tronco e força de preensão manual, contribui para o adoecimento no hospital pesquisado, representando um alto risco ergonômico (MACIEL, FERNANDES, MEDEIROS, 2006;MAGNAGO et al, 2007;PURIANE, 2008;PINHEIRO, TROCCOLI, PAZ, 2006 É importante destacar que a fisiologia do gênero feminino é diferente do masculino, quando expostos ao mesmo tipo de tarefa, a qual proporciona a utilização de força o gênero feminino terá que realizar um dispêndio biomecânico maior em relação ao gênero masculino (FERNANDES et al, 2010;LEVINE, 1993;RISING et al, 2005;MAGNAGO et al, 2007;LINNAMO et al, 2005). Sendo importante uma análise detalhada das tarefas com exigência de muita força quando for envolver o gênero feminino (REIS e MORO, 2012;REIS, et al, 2013).…”
Section: Figura 03 -Atendimento Do Paciente Na Utiunclassified
“…O tônus muscular básico e a capacidade de contração e descontração muscular permitem a manutenção dos sistemas de alavancas em diferentes posturas e a sua movimentação em movimentos (FERNANDES et al, 2010;LINNAMO et al, 2005). O comando nervoso de posturas e movimentos se da em parte pela ação da vontade consciente e em parte pela ação de sistemas automatizados e padronizados de resposta motor (MAGNAGO, 2007).…”
Section: Introductionunclassified